Grzeczność kluczem do zyskania przychylności słuchaczy w oparciu o wykłady Tadeusza Zielińskiego (1859–1944) - Szewczykowska, Anna (Collectanea Philologica, 2020)
Tadeusz Zieliński was an outstanding scholar specialising in Greek and Roman literature as well as an accomplished orator, though nowadays he is not always appreciated. The best example of his vast knowledge and oratorical talent is undoubtedly the cycle of eight lectures on the broadly conceived Antiquity. In those lectures, Zieliński discussed the ancient world in terms of scientific research, its influence on modern culture and its role in educating the young generation. In order to ensure the effectiveness of his message, he first had to win favour with the audience. His prestige in the scientific community greatly facilitated it, while the numerous rhetorical and linguistic devices he used guaranteed that his persuasive message brought the expected results. Coherent and logical composition, clear and vivid language, topoi, expressions and phrases aimed at reducing the distance between the sender and the receiver, adjusting the style to the audience, numerous examples, references to authoritative figures, among other things, played a vital role here. Such devices were as important as the contents of the text itself as they ensured the effectiveness of the communication.